Generalized Anxiety Disorder (GAD): Understanding Its Roots, Impact, and Modern Approaches to Treatment - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammed (Darul Yasin Al Sys, 2025)
Chronic worry and anxiety about particular areas of functioning or life shifts Characterizes GAD. Generalized anxiety disorder GAD remains one among the most widespread and enduring forms of anxiety disorder. GAD doesn’t arise out of thin air, but is often associated with deeper, systematic issues at hand. Not only does GAD affect one neurologically, but it impacts their emotional, social, and occupational functionality. Globally, millions face GAD. Furthermore, unlike anxiety regarding day-to-day things, GAD has no identifiable ‘weakness’ that triggers it, making it chronic in nature and extremely hard to control without professional support. In this article, I will aims towards incorporating the important aspects of GAD exploring its headline causes, diagnostic rules, prominent face, and fusion of treatment including modern medicine alongside proactive methods like exercise, psychotherapy, and self-help programs. Primarily focus is laid on CBT alongside mindfulness approaches, innovation due to neurobiology in treatment, and neurobiology’s impact on understanding and eradicating illness.